Development and characterization of sulfonated polyethersulfone membrane for proton exchange membrane fuel cell application - Mohd Azzarudin, Zailani (2010)
The objective of this studies is to develop and characterize sulfonated polyethersulfone membrane (SPES) for Proton Exchange Membrane Fuel Cell application. In the experiment, polyethersulfone were sulfonated with different reaction time before continue making the dope solution. The membranes were tested with water uptake, Differential Scanning Calorimeter (DSC) and Scanning Electron Microscopy (SEM) to analyze the membrane performance. The swelling test result showed that the value of water uptake % were directly proportional to the reaction time of sulfonation. Differential Scanning Calorimeter (DSC) result showed that higher reaction time of sulfonation, the higher of the glass transitions temperature (Tg) and melting temperature (Tm) of the SPES. SPES 6 sample gave the best result compared to the other samples with 63.13°C glass transition temperature and 92.87°C melting temperature. Scanning Electron Microscopy (SEM) showed that the membrane has symmetric structure.